Unveiling the dark side of tungsten: A comprehensive review of its toxicity - Huihui Du; Xiaoxuan Yu; Ting Yang; Lei Lu; Jing Sun; Hongxia Xie (Ecotoxicology and Environmental Safety)
Tungsten (W), a heavy metal with extensive industrial applications, has inadvertently been released into the environment yet received increasing attention regarding its potential toxicity to living organisms. In 2008, W was categorized as an emerging contaminant by the U.S. Environmental Protection Agency. Current research on its toxicity is fragmented, and the existing review papers and government reports, which primarily center on animal models, are often outdated. This review presents a comprehensive and systematic overview of the toxicity of W, particularly tungstate, to diverse biological entities including microorganisms, plants, animals, and humans. Notably, W holds biological significance in certain microorganisms but generally inhibits their growth and functions. High W exposure affects plant germination, growth, and nutrient absorption by disrupting transport and accumulation processes, and results in oxidative stress, root growth hindering, and vital enzyme disruption. In rodents, W accumulates in organs and is associated with tumor promotion, neurotoxicity, immunotoxicity, and reproductive implications. In humans, W exposure can compromise immune function, alter neurobehavioral patterns, and cause DNA damage, with potential carcinogenic effects, particularly in the lungs and bone marrow. This review consolidates recent toxicological findings and serves as a conceptual framework for future research on this emerging contaminant.